Developing an Intercultural-Based Text Book for Teaching Writing - Ila Amalia; As'ari As'ari; Uswatun Hasanah (Loquen, 2021)
Abstract: The spread of English as an international language has contributed to the current status of English teaching as a second or foreign language. This means that English teaching not only stimulates students to improve linguistic competence but also to enhance their intercultural competence. Teachers or designers must incorporate the cultural aspects as part of their teaching practices or teaching materials. This research aimed at (1) developing an intercultural-based textbook for teaching writing, (2) evaluating the feasibility of the intercultural-based textbook for teaching writing, and (3) evaluating the effect of the intercultural-based textbook on students’ writing skills. Twenty-one secondary school students participated as the subject of the research. Meanwhile, the ADDIE model (Analysis-Design-Develop-Implement Evaluate) was employed as its material development design. There were two experts who validated the textbook and an English teacher as the user. The result showed that an intercultural-based textbook was feasible to use for teaching writing. It was supported by the assessment results from the experts that were in the valid category. The use of the textbook also had an effect on students’ writing skills even in the low category. This could be seen from the post-test result that showed improvement compared to the pre-test result.Keywords: Intercultural competence, ADDIE Model, Writing Skill, Writing instruction, research, and development